Analysis of E-learning Program's Role in Physical Learning (Universitas Negeri Semarang, 2020)
This study aimed to determine the application of e-learning programs, the role of e-learning programs, and how important the e-learning program's role in Physical learning was. This research used descriptive study using 80 students of the odd semester in 2016/2017 and 2017/2018 academic study program. The data obtained by questionnaires then analyzed based on the specified categories. From the data processing, it was proved that e-learning programs could be applied through e-learning modules. The program's role was in the